2021
DOI: 10.3390/cancers13102330
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Microbiome in Liver Cancer

Abstract: Hepatocellular carcinoma (HCC) is the most common malignancy occuring in the context of chronic liver disease and is one of the main causes of cancer-derived death worldwide. The lack of effective treatments, together with the poor prognosis, underlines the urge to develop novel and multidisciplinary therapeutics. An increasing body of evidence shows that HCC associates with changes in intestinal microbiota abundance and composition as well as with impaired barrier function, leading to the release of bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 138 publications
0
13
0
1
Order By: Relevance
“…During the past decades, studies have indicated the potential role of gut microbiota in the pathogenesis of liver cirrhosis. Researchers have found the alterations of gut microbiota in patients with liver cirrhosis (Qin et al, 2014;Bajaj et al, 2021) and revealed the association between gut dysbiosis and its complications and poorer prognosis including liver failure and hepatocellular carcinoma (Bajaj and Khoruts, 2020;Moreno-Gonzalez and Beraza, 2021;Trebicka and Bork, 2021). Despite the increase of studies, gut microbiota was reported to involve in the development of liver cirrhosis, but which kind of microbiota and its role are still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, studies have indicated the potential role of gut microbiota in the pathogenesis of liver cirrhosis. Researchers have found the alterations of gut microbiota in patients with liver cirrhosis (Qin et al, 2014;Bajaj et al, 2021) and revealed the association between gut dysbiosis and its complications and poorer prognosis including liver failure and hepatocellular carcinoma (Bajaj and Khoruts, 2020;Moreno-Gonzalez and Beraza, 2021;Trebicka and Bork, 2021). Despite the increase of studies, gut microbiota was reported to involve in the development of liver cirrhosis, but which kind of microbiota and its role are still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Akkermansia muciniphila , a major propionate-producing bacterium, is recommended as a probiotic and an essential gut symbiont to maintain the metabolism homeostasis and alleviate obesity, diabetes, and liver diseases ( Mokhtari et al, 2017 ; Wang et al, 2019 ). FMT, a GM-altering approach, has been reported to reduce high-fat diet-induced steatosis, increase insulin sensitivity in patients with metabolic syndrome and improve the cognitive performance in cirrhotic patients ( Zhou et al, 2017 ; Moreno-Gonzalez and Beraza, 2021 ). Thus, studying the role of GM in NAFLD and the effect of specific intestinal flora in NAFLD patients will further help to diagnose and stratify patients and find therapeutic targets ( Kolodziejczyk et al, 2019 ).…”
Section: Gut Microbiota In the Pathogenesis Of Non-alcoholic Fatty Li...mentioning
confidence: 99%
“…Moreover, studies have shown that pathogenic Enterobacteriaceae as well as strains from oral microbiota, such as Veillonella and Streptococcus were enriched in patients with cirrhosis, consistent with the spread of bacteria from the mouth to the gut ( Chen et al, 2011 ; Qin et al, 2014 ; Yu and Schwabe, 2017 ). The GM composition of patients with cirrhosis showed relatively lower levels of Lachnospiraceae, Ruminococcaceae, Clostridialies XIV , and F. prausnitzii and a higher abundance of Bacteroidaceae ( Bajaj et al, 2014 ; Aron-Wisnewsky et al, 2020a ; Moreno-Gonzalez and Beraza, 2021 ). The microbial signature of cirrhosis showed high abundance of Megasphaera, Dialister, Atopobium, Prevotella , and Gallibacterium ( Chen et al, 2016 ; Caussy et al, 2019 ).…”
Section: Gut Microbiota-bile Acids Axis In the Progression Of Non-alc...mentioning
confidence: 99%
“…Gut microbes can change primary bile acids to secondary bile acids, leading to DNA damage, depletion in tumor-suppressing micro-DNA, alteration in numbers of NK T cells, and carcinogenesis [ 121 - 123 ]. Obesity resulting in nonalcoholic steatohepatitis (NASH) is also indirectly associated with gut dysbiosis leading to HCC [ 124 ].…”
Section: Reviewmentioning
confidence: 99%